2021
DOI: 10.3389/fmedt.2021.676025
|View full text |Cite
|
Sign up to set email alerts
|

Nanohybrids as Protein-Polymer Conjugate Multimodal Therapeutics

Abstract: Protein therapeutic formulations are being widely explored as multifunctional nanotherapeutics. Challenges in ensuring susceptibility and efficacy of nanoformulation still prevail owing to various interactions with biological fluids before reaching the target site. Smart polymers with the capability of masking drugs, ease of chemical modification, and multi-stimuli responsiveness can assist controlled delivery. An active moiety like therapeutic protein has started to be known as an important biological formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 142 publications
(191 reference statements)
0
7
0
Order By: Relevance
“…Since bioconjugation approaches are not the subject of this review, we refer the readers to existing reviews on the linkers and reactions that can be used. [89,90] In the field of physically entrapped proteins, drug release is mainly dependent on the diffusion of the proteins through the polymer network. Since this is similar to the loading process, parameters to control the release rate are the same as those discussed for the loading (Section 3.3.1.…”
Section: Release Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since bioconjugation approaches are not the subject of this review, we refer the readers to existing reviews on the linkers and reactions that can be used. [89,90] In the field of physically entrapped proteins, drug release is mainly dependent on the diffusion of the proteins through the polymer network. Since this is similar to the loading process, parameters to control the release rate are the same as those discussed for the loading (Section 3.3.1.…”
Section: Release Mechanismsmentioning
confidence: 99%
“…Since bioconjugation approaches are not the subject of this review, we refer the readers to existing reviews on the linkers and reactions that can be used. [ 89,90 ]…”
Section: Protein Encapsulation and Releasementioning
confidence: 99%
“…Further, polymer-based nanomedicines include polymer-protein conjugates and micelles. The conjugates provide protein drugs with targeting ability and enhanced circulation times (Kiran et al 2021 ). It has also been observed that such polymeric nanoparticles facilitate drug release for an extended time period (Kamaly et al 2016 ).…”
Section: Commercial Nanomedicine-based Formulationsmentioning
confidence: 99%
“…8 Until today, many more have followed 13−16 or are currently in clinical trials. 17 polymer conjugates hitherto approved by the FDA and is considered the gold standard for bioconjugation. PEGylation may reduce immunogenicity and extend in vivo half-life via a shielding effect against proteolysis and opsonization, as well as reduce renal filtration due to an increased hydrodynamic radius.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, protein biopharmaceuticals have been established as valuable alternatives to small-molecule drugs in different therapeutic areas. The application of such “biologics”, however, is faced with problems, as they are susceptible to degradation and aggregation phenomena ex vivo , and to proteolysis, immune responses and renal filtration in vivo . ,, Some of the problems can be circumvented through bioconjugation whereby the biological macromolecule is covalently linked to a synthetic, typically polymeric compound, with the aim of improving physicochemical and pharmacokinetic properties to overcome the therapeutic limitations of the unmodified variant. , The groundwork for this principle was laid in the early 1950s, , while studies with polyethylene glycol (PEG) in the late 1970s demonstrated its relevance for biomedical applications. , The first PEGylated drug, Adagen, was registered on the US market in 1990 . Until today, many more have followed or are currently in clinical trials . In fact, PEG has been used in all protein–polymer conjugates hitherto approved by the FDA and is considered the gold standard for bioconjugation.…”
Section: Introductionmentioning
confidence: 99%